Analysis of Clove Leaf Oil Distillation Business Income (Cloves Leaf Oil) In Matuo Sub-Village, Lelean Nono Village, Baolan District, Tolitoli Regency (Case Study of Tiga Jaya Essential Oil Refinery) - Ramlawati; Hilmi; Rani (Universitas Dwijendra Press, 2023)
Analysis of Clove Leaf Oil Distillation Business Income (Clove Leaf Oil) in Matuo Sub-Village, Lelean Nono Village, Baolan District, Tolitoli Regency (Case Study of Tiga Jaya Essential Oil Distillation), This study aims to determine how much Clove Leaf Oil Distillation Business Income (Clove Leaf Oil) in Matuo Sub-Village, Lelean Nono Village, Baolan District, Tolitoli Regency (Case Study of Tiga Jaya Essential Oil Distillation). This research uses a qualitative research design. The data source is primary data, namely data obtained through interviews and documentation related to this research. The data analysis method used is descriptive qualitative and quantitative, namely production cost analysis, business revenue analysis, income analysis, and R / C Ratio efficiency level analysis. After conducting research and discussions, it has been revealed that the Cloves Leaf Oil Distillation Business (Tiga Jaya Essential Oil Distillation) operating in Matuo Hamlet, Lelean Nono Village, Baolan District, Tolitoli Regency, During the 2022 period, a cloves leaf oil distillation business incurred a total cost of Rp. 993,196,500. The total revenue generated was Rp. 1,234,464,000. This indicates that the business earned a total income of Rp. 241,267,500 in one year. After conducting a case study of Tiga Jaya Essential Oil Distillation in Matuo Hamlet, Lelean Nono Village, Baolan District, Tolitoli Regency, the feasibility of Clove Leaf Oil Distillation Business for 2022 was found to have an R/C ratio of 1.24. The R/C Ratio of more than one indicates that the Cloves Leaf Oil Distillation Business located in Matuo Hamlet, Lelean Nono Village, Baolan District, Tolitoli Regency (as examined in the case study of Tiga Jaya Essential Oil Distillation) is viable and feasible